Marginality, security, surveillance, crime, imprisonment: Reflections on an intellectual and methodological trajectory - Frois, C. (Etnográfica, 2025)
This article engages with contemporary anthropological and ethnographic methodological debates by reflecting on the challenges of conducting research in contexts related with marginality, deviance, surveillance, and imprisonment. It examines the tensions surrounding access, researcher subjectivity, and the positionalities negotiated in the field, emphasizing the epistemological relevance of long-term ethnographic engagement. Rather than treating obstacles, disruptions, and moments of unpredictability as mere hindrances, it considers them as integral to the ethnographic process and as productive sites for generating insight.